Digitalisasi untuk Layanan Pendidikan di Fakultas Tarbiyah dan Ilmu Keguruan Iain Palangka Raya Tahun 2022 - Asmawati, Asmawati,; Samiyono Samiyono; Anwar Arifin; Iim Wasliman; Yosal Iriantara; Arman Paramansyah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Technology is always developing in every generation, as is the case with modern times like today, information can be obtained easily through digital technology systems. Various advantages and benefits obtained by its users because it is more effective and efficient. This then makes digital service-based information a crucial need for society, so that the need for digital-based information technology is able to penetrate boundaries and space so that it can be accessed from anywhere and at any time. FTIK IAIN Palangka Raya has implemented changes from this technology and digitized applications to improve educational services to students. This study aims to find out what media/applications are used and how they are applied by FTIK IAIN Palangka Raya in educational services to students. The research used is qualitative with a descriptive qualitative approach and analyzed through observation, interviews and documentation. The results of this study describe that the media / applications used by FTIK IAIN Palangka Raya are SIMAK and Website. FTIK IAIN Palangka Raya students feel satisfied and very helpful from an administrative point of view on the educational services they have experienced. Keywords: digitalization, educational services, media/applications.